1995
DOI: 10.1177/00220345950740021101
|View full text |Cite
|
Sign up to set email alerts
|

The Diffusion and Enzymic Hydrolysis of Monofluorophosphate in Dental Plaque

Abstract: Although the ability of dental plaque to hydrolyze sodium monofluorophosphate (MFP) has been known for some time, its effect on the F- concentration at the plaque-enamel interface is undefined. We have determined enzyme kinetic values for MFP hydrolysis and diffusion coefficients so that the penetration and degradation of MFP in plaque can be modeled by computer. The KM and Vmax values for natural human plaque were 1.77 mmol/L and 41.4 nmol/min/mg protein, respectively, at pH 8.0. At pH 6.0, the Vmax was lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 31 publications
2
12
1
Order By: Relevance
“…Our present experimental work confirms predictions that thicker plaque exhibits slower rates of permeation and increased hydrolysis [Pearce and Dibdin, 1995]. Diffusion and hydrolysis in the thicker plaque is probably more relevant to caries-prone areas of the dentition, i.e.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our present experimental work confirms predictions that thicker plaque exhibits slower rates of permeation and increased hydrolysis [Pearce and Dibdin, 1995]. Diffusion and hydrolysis in the thicker plaque is probably more relevant to caries-prone areas of the dentition, i.e.…”
Section: Discussionsupporting
confidence: 89%
“…In the mouth this activity is thought to be brought about by non-specific alkaline phosphatase of bacterial origin, since sterile duct saliva has no demonstrable alkaline phosphatase activity [Chauncey et al, 1963]. In the report of a computer simulation study we suggested that the enzymic hydrolysis of MFP within plaque, releasing fluoride and orthophosphate, is an important step in its anti-caries action [Pearce and Dibdin, 1995]. It has already been proposed on other grounds that the anti-caries activity of MFP may be due to fluoride [Grøn et al, 1971].…”
mentioning
confidence: 99%
“…Here again the high levels of MFP found in plaque fluid ( fig. 1) are relevant, and in agreement with these measurements, a recent diffusion-hydrolysis model for MFP in plaque [Pearce and Dibdin, 1995] …”
Section: Discussionsupporting
confidence: 85%
“…Specifically, NaMFP requires a hydrolysis step to release fluoride to the mouth whereas NaF does not. This hydrolysis step has been postulated [Pearce and Dibdin, 1995] as a major reason for the observation that NaF dentifrices generally show higher salivary and whole plaque fluoride concentrations than NaMFP dentifrices [Duckworth et al, 1994]. In spite of these results, clinical studies have yielded somewhat ambiguous results …”
mentioning
confidence: 99%
“…The mathematical model used is based on that described by Dibdin [1990] for modelling a cariogenic challenge and that of Pearce and Dibdin [1995] for modelling the diffusion of monofluorophosphate into dental plaque, and its subsequent hydrolysis. The model includes the salivary clearance of sugar from the mouth; site-dependent exchange between the bulk saliva and the plaque surface via a salivary film; sugar diffusion into plaque and pH-dependent acid formation; diffusion and dissociation equilibria for the acid end-products and other buffers (acetate, lactate, phosphate and carbonate); the diffusion of protons and other ions and their simultaneous equilibration with fixed and mobile buffers.…”
Section: Methodsmentioning
confidence: 99%